Single nucleotide polymorphisms in northeast European wolves (Canis lupus) - Fröstl, Federico Javier (2013)
In the 1960s, the gray wolf was extinct as a breeding population in Scandinavia. However, in the 1980s a pair was established and started to reproduce in central Sweden. A third wolf, a male, immigrated to Sweden in 1991 contributing to the genetic variation in Scandinavia. Currently the Scandinavian wolf population consists of more than 280 individuals. The population is thus a typical example of a population that has undergone a severe bottleneck. To define the degree of genetic variation in the Scandinavian wolf population thought regions of homozygosity (ROH) and to evaluate possible contribution of immigrant individuals to increase genetic variation on the Swedish population, twenty-three wolves have been genotyped using the 170k canine-specific single nucleotide polymorphism (SNP) array. SNP data was analyzed with PLINK [1] and R [2] software’s.